Health promotion for dementia risk reduction in First Nations populations of Canada, Aotearoa New Zealand, United States of America, and Australia: Scoping review protocol. ... - Meldrum, Kathryn (OSF Registries, 2024)
Health promotion programs and strategies have the potential to support people to live healthier lives. Dementia, a collective name for brain disorders that impact thinking and memory, affects over 55 million people worldwide. Currently, there is no cure for dementia, so prevention is critical. Health promotion has the potential to reduce dementia by targeting the twelve potentially modifiable risk factors. A project currently being undertaken by the research team aims to strengthen the quality of clinical care and health services that specifically address dementia risk for Australian Aboriginal and Torres Strait Islanders. One of the intended strategies supporting the project’s aim is the need for appropriate and safe health promotion programs and resources that support dementia risk reduction. Consequently, the aim of this scoping review is to identify and determine the quality and appropriateness of existing health promotion programs and resources aimed at dementia risk reduction developed or modified for ...